Blasting optimization with the use of pumpable emulsion in underground mining and tunneling - Cahuata Esquivel, Michael (2021)
The objective of this work was to show the optimization generated by the implementation of the pumpable emulsion in underground mining and tunneling; having as scientific basis the technical studies carried out in the mining units: Condestable, Pallancata, Huarón and Andaychahua. In order to obtain: a reduction in operating costs, mitigation of polluting gases and reduction of the damage induced to the rocky massif; It was proposed to replace our Emulnor baseline with an explosive that would allow us to achieve the aforementioned objectives, concluding after various tests that the best optimization alternative was provided by Emulfrag, since compared to the baseline, it allowed us to generate savings of 26.9 USS / m for soft rock, 26.9 USS / m for medium rock and 26.9 USS / m for hard rock; Regarding polluting gases, the emission of carbon monoxide was reduced by 55.3% and by an average of 70.2% of nitrous gases, the reduction of gases from plastic combustion was achieved; Thanks to the deflagrating effect produced by Emulfrag at 0.8 g / cm3, the area of ​​intense fracturing was reduced by 30 cm and the area of ​​creation of new fractures was reduced by 10 cm.